Implementation of Increasing Sales and Work Productivity of MSMEs Patchwork Mats in Gondangrejo Village - Afif, Naufal; Syahbani, Evan Nur; Imana, Muhammad Tsabit; Nisa, Zahra Aisy Khairin; Lestari, Alfi Dina; Mustaqim, Alif (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The purpose of this service is to provide socialization, training, and rebranding for UMKM Keset Abadi Dusun Bekelan that with digitalized marketing and good branding it will be able to expand the range of customers from the products sold and also retain existing consumers. The method used to achieve this goal is to carry out two service activities, namely socialization and training, as well as product rebranding. The results achieved are the understanding and knowledge of the UMKM Keset Abadi business actors in operating social media as a means of digital marketing.